2016
DOI: 10.18383/j.tom.2016.00169
|View full text |Cite
|
Sign up to set email alerts
|

Accrual Patterns for Clinical Studies Involving Quantitative Imaging: Results of an NCI Quantitative Imaging Network (QIN) Survey

Abstract: Patient accrual is essential for the success of oncology clinical trials. Recruitment for trials involving the development of quantitative imaging biomarkers may face different challenges than treatment trials. This study surveyed investigators and study personnel for evaluating accrual performance and perceived barriers to accrual and for soliciting solutions to these accrual challenges that are specific to quantitative imaging-based trials. Responses for 25 prospective studies were received from 12 sites. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…With additional procedures and administration of imaging agents, trials involving the development of new QI methods/tools may face more challenges in patient recruitment. The CTDDWG surveyed 25 prospective clinical studies from 12 sites to evaluate the accrual performance, barriers, and solutions that are specific to QI-based trials (6). Our findings showed that the median percent annual accrual attained was 94.5% (range, 3%-350%).…”
Section: Identify Challenges and Opportunities In Clinical Trial Design And Developmentmentioning
confidence: 91%
“…With additional procedures and administration of imaging agents, trials involving the development of new QI methods/tools may face more challenges in patient recruitment. The CTDDWG surveyed 25 prospective clinical studies from 12 sites to evaluate the accrual performance, barriers, and solutions that are specific to QI-based trials (6). Our findings showed that the median percent annual accrual attained was 94.5% (range, 3%-350%).…”
Section: Identify Challenges and Opportunities In Clinical Trial Design And Developmentmentioning
confidence: 91%